Lipoprotein(a) and residual vascular risk in statin-treated patients with first acute ischemic stroke: A prospective cohort study - Wang, Lanjing; Liu, Lijun; Zhao, Yanhong; Chu, Min; Teng, Jijun (Frontiers in Neurology, 2022)
Objectives: Statins either barely affect or increase lipoprotein(a) [Lp(a)] levels. This study aimed to explore the factors correlated to the change of Lp(a) levels as well as the relationship between Lp(a) and the recurrent vascular events in statin-treated patients with first acute ischemic stroke (AIS). Methods: Patients who were admitted to the hospital with first AIS from October 2018 to September 2020 were eligible for inclusion. Correlation between the change of Lp(a) levels and potential influencing factors was assessed by linear regression analysis. Cox proportional regression models were used to estimate the association between Lp(a) and recurrent vascular events including AIS, transient ischemic attack, myocardial infarction and coronary revascularization. Results: In total, 303 patients, 69.6% males with mean age 64.26 ± 11.38 years, completed the follow-up. During the follow-up period, Lp(a) levels increased in 50.5% of statin-treated patients and the mean percent change of Lp(a) levels were 14.48% (95% CI 6.35% - 22.61%). Creatinine (β = 0.152, 95% CI 0.125-0.791, P = 0.007) and aspartate aminotransferase (AST) (β = 0.160, 95% CI 0.175-0.949, P = 0.005) were positively associated with the percent change of Lp(a) levels. During a median follow-up of 26 months, 66 (21.8%) patients had a recurrent vascular event. The median time period between AIS onset and vascular events recurrence was 9.5 months (IQR 2.0 – 16.3 months). The on-statin Lp(a) level ≥70 mg/dL (HR 2.539, 95% CI 1.076-5.990, P = 0.033) and the change of Lp(a) levels (HR 1.003, 95% CI 1.000-1.005, P = 0.033) were associated with the recurrent vascular events in statin-treated patients with first AIS. Furthermore, the on-statin Lp(a) levels ≥70 mg/dL (HR 3.612, 95% CI 1.018-12.815, P = 0.047) increased the risk of recurrent vascular events in patients with low-density lipoprotein cholesterol (LDL-C) levels < 1.8mmol/L. Conclusions: Lp(a) levels increased in half of statin-treated patients with first AIS. Creatinine and AST were positively associated with the percent change of Lp(a) levels. Lp(a) is a determinant of residual vascular risk and the change of Lp(a) is positively associated with the risk of recurrent vascular events in these patients.